Development Of Domino Card Media In Vocabulary Learning For Students At Islamic Junior High School State Of 2 Bondowoso - Fitria Cinta; Asep Maulana; Maskud, Maskud (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Vocabulary is the most important element in language and can be the main factor that leads to understanding the meaning of sentences in communication situations or in understanding reading texts. In fact, ninth semester students (I) of Islamic Junior high School State of 2 Bondowoso are lazy about teaching vocabulary, let alone memorizing and repeating it, because they have no desire to learn it, they see it. difficult to learn, and they feel bored because the teaching is monotonous. Researchers were able to develop the domino card method for teaching vocabulary. The research objectives of this study are 1) to determine the development of the domino card method in teaching vocabulary to students at Islamic Junior high School State of 2 Bondowoso, 2) to determine the validity of domino card media in teaching vocabulary to students there, 3) to determine the effectiveness of domino card media in vocabulary learning to students in it. The research methodology used is research and development with the ADDIE model. The data used is qualitative and quantitative, and the data collection tools are observation, interviews, questionnaires, tests and documentaries. The sample used was 33 students. The data analysis method used is descriptive and SPSS 23.0.1.0.. The results of this research: 1) The development of the domino card method for teaching vocabulary was carried out through designing domino cards containing the vocabulary taught to students. 2) The validity of the assessment data from educational material experts is 95.8% and educational methods experts are 93.7%. This indicates that the product is at the “very good” level. 3) The t test (calculation) shows a value (sig) of less than 0.005, namely 0.000. Apart from that, the calculated t value was 20.302 and the t table degree was obtained. is at a significance level of 5% = 1.697, then the calculated t score is greater than the t table so that H0 is rejected and Ha is accepted for ninth grade students (I) of Islamic Junior high School State of 2 Bondowoso.